Correlation of Serum Interleukin-6, TNF-Î±, Procalcitonin and Leukocyte Count in Patients with Suspected Sepsis - Erfina Lim; Jusak Nugraha (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Sepsis is a cause of non-cardiac death in the hospital. Early and rapid diagnosis of septic patients is a challenge to increase the expectancy of life. IL-6 and TNF-Î± are groups of pro inflammatory cytokines that initiate an initial inflammatory response. Procalcitonin is a specific marker of bacterial infection. This study aimed to analyze the correlation of serum cytokine IL-6, TNF-Î±, procalcitonin and leukocyte count in suspected sepsis patients. This was a cross-sectional observational study consisting of 45 patients with suspected sepsis with procalcitonin level > 0.5 ng/mL. Procalcitonin level was measured with Enzyme-Linked Fluorescent Assay (ELFA) (VIDAS), IL-6 and TNF-Î± levels were measured with theU-CyTech Human Elisa kit (Bioscience, INC) and leukocyte counts were measured with SYSMEX-XN 1000. It was found in this study that IL-6 levels ranged in 0 pg/mL – 73.29 ng/mL (mean 29.43 ng/mL), TNF-Î± levels were 0 pg/mL – 390.5 pg/mL (mean 27.62 pg/mL), and the mean value of leukocytes was 20,139/Î¼L. There was no correlation between leukocyte counts with IL-6 (p=0.798 and r=0.040), TNF-Î± (p=0.304 and r = -0.160), and procalcitonin (p=0.323 and r = 0.154). There was no correlation between IL-6 levels with TNF-Î± levels (p=0.871 and r = -0.025), and procalcitonin levels (p = 0.466 and r = 0.112). There was a weak negative correlation between TNF-Î± level and procalcitonin levels (p=0.006 and r = -0.403) and there was a weak negative correlation between procalcitonin and TNF-Î± levels in suspected sepsis patients.